Shiga-toxin Escherichia coli contamination in cattle post harvest - Noviyanti, Fnu (Kansas State University, 2018)
Among animal products consumed by humans, ground beef has been reported as one of the most common vehicles for STEC outbreaks in humans. In the United States, cull dairy cattle contribute as one of the primary sources for ground beef. The objective of this study was to determine the prevalence and concentration of 7 Shiga toxin-producing Escherichia coli serogroups (STEC-7; O26, O103, O111, O121, O45, O145, and O157) and associated virulence genes (Shiga toxin 1 and 2 (stx1, stx2), intimin (eae), and enterohomolysin (ehxA)) in the feces of cull dairy cattle processed in commercial slaughter plants during summer months. Fecal swab samples (n=183) were collected from three processing plants, one in California and two in Pennsylvania. At each plant at least 60 to 65 cattle were selected, and the samples were obtained by swabbing the mucosal surface of the recto-anal junction using a sterile cotton-tipped applicator. To determine prevalence, all samples were subjected to culture-based detection methods that included enrichment, serogroup-specific immunomagnetic separation and plating on selective media, followed by polymerase chain reaction for serogroup confirmation and virulence gene detection. Pre-enriched fecal samples were subjected to spiral plating to determine the concentration of STEC-7. A sample was considered STEC positive if a recovered isolate harbored one of the 7 target O genes, stx1, and/or stx2. Of the 183 fecal swab samples collected, 23 (12.6%) harbored at least one O157, O26, O103, or O111 serogroup, with their associated virulence genes. However, none of the fecal samples from this cattle population carried STEC at high-levels (>10⁴ CFU/g). This study has provided important information on STEC-7 prevalence from dairy cattle that enter the ground beef processing system. However, there is still a need to determine prevalence and concentration of STEC in cull dairy cattle during winter months as well as in other sources of ground beef production (e.g., imported lean beef, cull beef).
Keywords: Shiga-toxin Escherichia coli; STEC; Cattle; Prevalence; Concentration